Gene-gene Interaction in Cerebral Infarction Patients : A Study on Relationship Between Apolipoprotein E, ACE Gene Polymorphism and Sasang Constitution - Kim Jong Kwan; Kim Hyoung Soon; Bae Young Chun; Lee Sang Min; Kim Kyung Yo; Joo Jong Cheon (동의생리병리학회지, 2004)
Sasang Constitutional Medicine is a major branch of Korean Traditional Medicine. The differences of disease susceptibility to be shown in Sasang constitution may be due to genetic factors. Therefore, I examined interrelationship among cerebral infarction (CI), apolipoprotein E (apo E) gene polymorphism, and Sasang constitutional classification. Apo E is a key protein modulating the highly atherogenic apoB containing lipoproteins and is a candidate gene for the development of coronary artery disease (CAD). The ε2 and/or ε4 alleles were the first to be implicated in premature CAD, which resulted in this polymorphism being extensively studied. I investigated the association between apo E genotype and CI by case-control study in a Korean population. I also classified CI patients and control group into groups according to Sasang Constitutional Medicine. 218 CI patients and 379 controls without CI were examined. Apo E genotype was determined by 8% polyacrylamide gel separation after DNA amplification. A frequency of apo E ε3/ε3 in the apo E genotype distribution was higher in the CI patients compared with that in controls. Also, it was widely known that Taeumin was easily attacked with CI, but there was no association between apo E polymorphim and Taeumin. However, the Taeumin constitution did not enhance the relative risk for CI in the subjects with apo E ε2 and/or ε4 alleles. No differences in the apo E genotypes frequencies were observed in the Taeumin compared with that in the other constitutions. In addition, I investigated whether the DD(deletion/deletion) or ID(insertion/deletion) genotype of angiotensin converting enzyme (ACE) gene, a candidate gene for CI, was associated with CI, Taeumin constitution, and apo E polymorphism. As a result, the frequency of Taeumin constitution was significantly higher in CI patients with both apo E ε3/ε4 and ACE ID/DD genotypes than in the remaining Sasang constitutions. In summary, it was concluded that the apo E polymorphism is a major risk factor for CI in Koreans and the ACE ID/DD genotype enhanced the relative risk for CI in the subjects with apo E ε3/ε4 genotype and Taeumin constitution.